Correlation Analysis of The Community Led Total Sanitation with Diarrhea Services in West Nusa Tenggara Province in 2019 - Heru Saprudin; Fariani Syahrul (Health Notions, 2021)
Diarrheal disease is an environmentally based disease. Diarrheal diseases in Indonesia have the potential to cause Extraordinary Events (KLB) because diarrhea is endemic and environmentally based which is often accompanied by death. This study aims to Analyze The Relationship of Community-Led Total Sanitation (CLTS) and Open Defecation Free (ODF) with The Scope of Diarrhea services in West Nusa Tenggara Province in 2019. This type of research is observationally descriptive with cross sectional design. This study uses secondary data from the 2019 Profile of the West Nusa Tenggara Provincial Health Office that has been published in the West Nusa Tenggara Provincial Health Office. The data analysis technique used is a correlation test to see the strong relationships between variables. The results showed the STBM Program with Diarrhea service coverage in West Nusa Tenggara Province in 2019 had a very strong relationship with a correlation value of 0.863. The Stop BABS program with coverage of Diarrhea services in West Nusa Tenggara Province in 2019 had a strong relationship with a correlation value of 0.699. The conclusion of this study is that there is a very strong relationship between the STBM program and the coverage of diarrhea services in NTB and there is a strong relationship between the Stop BABS program and the coverage of diarrhea services in NTB.Keywords: CLTS; ODF; diarrhea services